Fossoriality in a risky landscape: badger sett use varies with perceived wolf risk. (3rd October 2020) - Diserens, T. A.; Bubnicki, J. W.; Schutgens, E.; Rokx, K.; Kowalczyk, R.; Kuijper, D. P. J.; Churski, M.
Abstract: Many medium‐sized carnivores are fossorial and use burrow systems to reduce predation risk or avoid predators. But fossorial species cannot stay safely underground forever, and they must also risk emerging overground, to forage and find mates. To make this trade‐off effectively and maximize their own fitness, it is imperative they assess how predation risk varies in space and time, and adapt their denning behaviour accordingly. We used European badger ( Meles meles ) burrows (setts) in Białowieża Forest, Poland as a model for investigating how the denning behaviour of a fossorial mesocarnivore varies across gradients of landscape scale perceived risk imposed by wolves ( Canis lupus ) and humans, defined as wolf space use and distance to settlements, respectively. We monitored seventeen setts with varying levels of perceived human and wolf risk with camera traps for two months to study three denning behaviours: frequency of badger sett use, frequency of badger sett sharing with other mesocarnivore species and badger emergence time. Frequency of sett use varied relative to perceived wolf but not human risk. Setts in the highest risk areas were used ca. 60% less often than those in the lowest perceived risk areas, and setts with juveniles were only present in areas of lower perceived risk. Food availability, quantified as earthworm abundance in an area of 2.1 km 2 around setts, did not affect the frequency setts were used. Emergence time and frequency of sett sharing with other mesocarnivores, which have been proposed to be anti‐predator strategies, did not vary with either perceived risk factor. These results show fossorial species can adapt their use of burrows to the prevailing risk landscape and suggest burrows deserve more attention in studies on the ecological impacts of apex predators. Abstract : To maximise their fitness, it is imperative fossorial species assess how predation risk varies in space and time, and adapt their denning behaviour accordingly. We studied seventeen European badger setts in Białowieża Forest with camera traps to investigate how the denning behaviour of this fossorial mesocarnivore varies across gradients of landscape scale perceived risk imposed by wolves and humans. Setts in the highest wolf risk areas were used ca. 60% less often than those in the lowest perceived risk areas, and setts with juveniles were only present in areas of lower perceived risk. Perceived human risk and earthworm abundance in the vicinity of setts did not affect the frequency setts were used. These results suggest fossorial species can adapt their use of burrows to the prevailing risk landscape and indicates burrows deserve more attention in studies on the ecological impacts of apex predators.